PENGARUH MOTIVASI, KOMPENSASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. ADIRA DINAMIKA MULTI FINANCE Tbk SEMARANG - Rian Tri Laksono, 06.05.51.0076; Waruwu, Penunjang (Students Journal of Economic and Management, 2013)
The study entitled " The effect of motivation, compensation and leadership to employee performance at pt. Adira dinamika multi finance tbk semarangâ. The population in this study is employee of Adira dinamika multi finance tbk semarang. Sampling is done by using "purposive sampling", ie the sampling technique based on chance and the number of samples taken as 100.The collected data were analyzed using factor analysis to test the validity of the statement items, Cronbach alpha formula to test the reliability of the instrument, the regression analysis to examine the influence of each partial independent variables were tested with the coefficient of determination and test fit the model to test and prove the influence of the Partial each independent variable. The results of the study are: (1) The results of the statistical linear regression analysis can be shown by the regression equation Y= 0,348 X1 + 0,273 X2 + 0,275 X3. From the regression equation it is known that the motivation, compensation and leadership has a positive and significant impact on employee performance. (2) The calculation of the coefficient of determination result is 0.600. This shows that the motivation, compensation and leadership variables could explain 60.% of employee performance, while the remaining 40.0% is explained by other variables not included in this study. (3) The hypothesis that has been done in this study are: a) positive effect on motivation to employee performance at pt. Adira dinamika multi finance tbk semarang. b) positive affect compensation to employee performance at pt. Adira dinamika multi finance tbk semarang. c) positive affect leadership to employee performance at pt. Adira dinamika multi finance tbk semarang. In this study the variable motivation has a more dominant effect than compensation and leadership.Key words: Motivation, Compensation, Leadership and Employee Performance.